(untitled) (Research, Society and Development, 2021)
Pertussis is an acute, transmissible disease of universal distribution. It specifically compromises the respiratory tract (trachea and bronchus) and is characterized by paroxysm of dry cough. This study aims to describe the epidemiological aspects of pertussis in the state of Piauí, Northeast Brazil, from 2013 to 2018. The data were taken from the clinical reports of the Notifiable Diseases Information System (SINAN). Descriptive analyses of the numbers of reported cases of pertussis were performed, according to age group, sex and municipality most affected, as well as clinical evolution. From 2013 to 2018, 688 confirmed cases of pertussis were reported in Piauí. The state capital presented the highest notification number of 617 cases. According to the age group, the largest number of notifications is for children under 1 year old with 328 cases, followed by children aged 1 to 4 years with 103 cases. Regarding gender in most notifications women are the most affected. Pertussis is a disease that occurs in endemic and epidemic forms, has increased its indications during the years but have vaccination in the SUS calendar in children for its prevention.